Analysis of Lead (Pb) content in the tissues of kipar fish (Scatophagus argus) from the Waters of Muara Pantuan Village, Kutai Kartanegara Regency - Musyarif, Muhammad Maksum; Eryati, Ristiana; Ritonga, Irwan Ramadhan (Acta Aquatica: Aquatic Sciences Journal, 2026)
The spotted scat (Scatophagus argus) is a nutrition source in the waters of Muara Pantuan, Mahakam Delta. However, anthropogenic activities from land have caused Lead (Pb) contamination in these waters, which has the potential to accumulate in fish. The purpose of this study was to determine Pb concentrations in various tissues of the spotted scat and analyze the associated human health risks from its consumption. A total of 8 fish samples were collected from Muara Pantuan waters with the assistance of local fishermen. Gill, digestive organ, and muscle tissues were digested using the acid digestion method, and Pb concentrations were analyzed using an Atomic Absorption Spectrophotometer (AAS) type iCE 3000. The results show the highest Pb concentration was found in the gills (0.04 ± 0.01 µg/g dry weight), while the lowest was in the digestive tract (0.03 ± 0.01 µg/g dry weight). The mean Pb concentration across all fish tissues ranged from 0.02 to 0.05 µg/g dry weight, which remains below the Indonesian National Agency of Drug and Food Control's (BPOM) standard of 0.20 µg/g. Correlation analysis between Pb and length (r = 0.80) and weight (r = 0.75) of the spotted scat showed a negative relationship with a strong correlation coefficient, but the relationship was not significant (p > 0.05). The Maximum Weekly Intake (MWI) calculation yielded the highest safe consumption limit for the adult group (43.8 kg/week), followed by adolescents (35.7 kg/week), and children (10.9 kg/week). Based on Pb concentration and health risk analysis, the spotted scat from Muara Pantuan waters is still considered fit and safe for human consumption. Keywords: Fish; Heavy Metal; Mahakam Delta; Risk Health